Translation and Validation of Barthel Index in Urdu Language for Stroke Patients - Kashmala Mustafa, Shoaib Waqas, Rida Khawar Dar, Rida Khawar Dar, Qurat Ul Ain Sherazi, Muhammad Tariq, Hafiz M. Asim (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To translate and validate of Barthel index in Urdu language for stroke patients Methodology: From June 2020 to January 2021, a descriptive linguistic validation research was done using convenient sampling at Ghurki Trust and Teaching Hospital in Lahore. Twenty neurological rehab professionals and 200 stroke survivors who could understand Urdu were used to validate the content. Two translators, one with a medical background and the other with a technical background in Urdu language, forward translated the BI English version into Urdu. The backward translation of the translated versions BI-Urdu-I and BI-Urdu-II into English was done by two professionals with medical and technical backgrounds who are fluent in Urdu to English translation. After that, the re-translated versions BI-English-III and BI-English-IV were compared to the original BI-English (English version) by expert committee. Data was collected by Final version of Urdu while considering inclusion and exclusion. Patients gave their consent in advance, and anonymity was guaranteed. Results: The mean age of stroke patients was 54.87 and standard deviation was 0.7648. The Chronbach’s alpha of translated version of BI questionnaire is 0.732. The inter item correlation (Pearson Correlation) after testing and re-testing on stroke patients was ranged from (0.425-0.945). The Intra-class Correlation after the translation of BI ranged from 0.314-0.732. Conclusion: Urdu version of Barthel index is a valid and reliable tool for stroke patients.